P-10 Latin American registry of cholangiocarcinoma: clinical features, management and outcomes - De Fonseca, Leonardo G. (2021)
Abstracts of the 2021 Annual meeting of the ALEH (Asociación Latinoamericana para el Estudio del Hígado)